ECONOMIC DEVELOPMENT AND DEMOCRACY IN EMERGING ECONOMIES - Rabia Efeoğlu; Sabri Azgün (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of this study is to investigate the effects of economic development on democracy with the data for the period 2001-2016 in 24 emerging market economies. This article develops a new methodology and analyzes the impact of openness, economic, social and financial development indicators on the level of democracy. We used the panel-ordered qualitative preference analysis method to estimate the relationship between democracy and economic development. We have concluded that economic development is more effective at higher levels of democracy and is higher likely to affect the higher level of democracy. We have shown that economic development raises the level of democracy.